IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH COMMUNICATIVE LANGUAGE TEACHING METHOD AT SMP 1 KUPANG - Pajangu, Priska R. B; Kamengko, Daniel Frengki; Tamelan, Thersia Magdalena (Journal of Language, Education, Literature, and Culture, 2024)
Speaking skill is one of the four essential skills in English. However, some students need help with their speaking ability. This research used the communicative language teaching (CLT) method to teach English, specifically by utilizing picture series to help students improve their speaking skills. This study aimed to determine whether the CLT method enhances students' speaking skills. An experimental design was employed for this research. The population of this study consisted of 353 students from grade 8 of Public Junior High School 1 Kupang. The cluster random sampling technique was employed to select a sample of 32 students. The data collection process involved a spoken test, pre-test and post-test to assess students' speaking skills. The results of the data analysis indicate that the mean score of students on the pre-test was 7.81. After the intervention, the mean score of students on the post-test was 17.34, and there was an improvement of 12.2%. The data was analyzed using a t-test; the t-test value (5.21) was more significant than the t-table value (1.69552). Therefore, the alternative hypothesis (H1) was accepted, and the null hypothesis (Ho) was rejected. The findings demonstrated that the CLT method effectively enhanced students' speaking skills.